Qualitative and Quantitative Analysis of Antioxidant in Panicum sarmentosum - Nur Azrin Shahir (2018)
Panicum sarmenzosum is a medicinal plant which grows in various areas of Kelantan and is consumed without knowing its nutritional value. This study deals with the qualitative and quantitative analysis of P. sarmentosum. The qualitative results revealed that aqueous extract of Panicum sarmentosum contained ﬂavanoids, saponins, tannins, phlobatannins, terpenoids and cardiac glycosides. Meanwhile, ethanolic extract shows negative results for terpenoids and cardiac glycosides. Quantitative analysis revealed 23.42% alkaloids, 18.51% saponins, 2.69 mg GAE/g tannins, 0.932 mg GAE/g phenolic content, 19.43 mg QE/g ﬂavonoid content, and 14 mg AA/g vitamin C. As for in vitro analysis using DPPI-l test, the extract exhibited 39% scavenging activity. The presence of beneﬁcial phyto-constituents and the ability to scavenge free radicals suggested P. sarmentosum can be exploited as a new good source of supplements